Assessing Kurt Goldstein’s lasting influence in the neuropsychology of language versus his use of aphasic symptoms as diagnostic insights into brain injuries - Stahnisch, Frank W. (Frontiers in Psychology, 2024)
In the history of the neurological relationship between human behavior and brain function in Europe and North America, various perspectives on brain localization and holistic functioning have been addressed. One of the founding figures of modern neuropsychology, Professor Hans-Lukas Teuber (1916–1977) of the Massachusetts Institute of Technology, reminded the scholarly community of its negligence of preceding traditions in day-to-day research endeavors. Teuber particularly emphasized that during the development of the aphasiology field (1950s–1960s) even major figures, such as the German-American neurologist Kurt Goldstein (1878–1965), had been neglected in the scientific community’s collective memory. This happened despite Goldstein’s contributions to cortical blindness, vicarious brain functioning, and neurorehabilitation. The outcome of the debates regarding the neurology of language had to be incompletely relearned in later decades. Neuropsychological concerns regarding the relationship between cortical localizationism and functional holism have made recourse to Goldstein’s work necessary for reviving historical answers for current conundrums. It is therefore opportune to review Goldstein’s work in the light of the history of aphasiology. Contemporary scholarship has once more drawn research attention to the works of Goldstein along with Norman Geschwind (1926–1984) and his pupils. It has also resurrected the underlying research of Carl Wernicke (1848–1905). This review article explores deep and lasting questions regarding the positioning of Goldstein’s holism among the contemporary holistic perspectives. It does so by firstly discussing Wernicke’s traditional model of distributed localizationism. Secondly, it describes Goldstein’s previous work in the German brain sciences. Thirdly, it examines his aphasiological contributions on both sides of the Atlantic. Fourthly, it addresses the advancement of a dynamic localizational perspective by Geschwind and his pupils. This article intends to render a historical analysis fruitful for those exploring modern-day problems in the neurology of aphasia and clinical speech neuropsychology.